Mothers in the Jazan Region of Saudi Arabia: Their Knowledge and Practices Regarding Diaper Dermatitis - Mai Mustafa; Gassem Gohal; Sami Alhazmi; Hussain Moafa; Nasser Hadi Ibrahim Sobaikhi; Musab Yahya Lahiq Dallak; Joud Alamri; Abdullah Alqahtani; Mohammed Matari; Khlood Khalid Alattas; Shouq Hakami; Rakan Hazazi; et al. (Hail Journal of Health Sciences)
Background: Diaper dermatitis (DD) is a prevalent condition causing discomfort in infants, linked to both care practices and sociocultural factors. This study assesses the knowledge and management practices of DD among mothers in the Jazan region, Saudi Arabia, aiming to identify the associated factors with maternal knowledge. Materials and Methods: A cross-sectional, descriptive survey was conducted using a self-administered, validated online questionnaire. Participants included 417 mothers from Jazan region, utilizing a nonprobability convenience sampling technique. Data on sociodemographic variables, childcare practices, and knowledge of DD were collected and analyzed using the SPSS software version 27.0. Results: Most mothers (94.0%) showed good knowledge of DD, with correct identification of its causes and prevention methods. Older mothers and those with 3–5 births demonstrated better awareness. Regular prenatal visits and acquiring knowledge from experienced relatives were significantly associated with higher knowledge levels. However, knowledge gaps existed regarding the impact of cloth diapers and the need for timely medical consultation for DD. Conclusion: The study revealed a commendable level of maternal knowledge about DD, with certain demographic factors such as age and birth number playing a significant role in knowledge variance. The insights emphasize the need for targeted educational efforts to address specific misconceptions and improve DD management practices. Enhanced community health education could improve care practices and outcomes for infants with DD in Jazan.